(untitled) (South Asian Journal of Agriculture, 2025)
An experiment was conducted in the Plant Protection Laboratory of Agrotechnology Discipline, Khulna University, Khulna, Bangladesh to evaluate the sensitivity of Trichoderma harzianum to seeds and soil treating chemicals namely, Carbendazim (Bavistin), Mancozeb (Dithane M-45), 64% Mancozeb + 8% Metalaxyl (Ridomil 68 WP), Iprodione (Hayprodione 50 WP), Carboxin + Thiram (Provax 200 WP), Carbofuran (Furadan 5G), and Calcium hypochloride (Bleaching powder). All tested chemicals were applied at three concentrations: Bavistin, Dithane M 45, Ridomil, Hepridione 50 WP, Provex, and Furadan 5G at 1000, 2000, and 3000 ppm; and Bleaching powder at 25, 50, and 100 ppm. Results revealed that mycelial growth of T. harzianum was inhibited 100% at all concentrations of Bavistin, Hayprodione 50 WP and Provex. However, Mancozeb inhibited 100% mycelial growth at 3000 ppm concentration and 66.80% at 2000 ppm (recommended dose). At the recommended dose, Ridomil, Furadan 5G, and Bleaching powder inhibited mycelial growth of T. harzianum by 24%, 14.60%, and 22.60% respectively. Across different concentrations, Mancozeb, Ridomil, Carbofuran, and Bleaching powder showed inhibition rates of over 98%, 82%, 91%, and 83% respectively. These results suggest that T. harzianum is highly sensitive to Bavistin, Provex, Hepridione 50 WP, and Dithane M 45, while it shows relatively low sensitivity to Ridomil, Furadan 5G, and Bleaching powder at the recommended dose. South Asian J. Agric., Vol. 11, No.1, 2025: 38-44